Oral Hygiene Status and Caries Experiences Among Smoker Male in Associated with Their Knowledge in Benghazi City, Libya. - Ayyad, Halima; Hawwa Beaayou; Hanan Ghaith (AlQalam Journal of Medical and Applied Sciences, 2025)
Smoking has negative effects on health in general, and it is considered a risk factor for death. Much of the research evidence that smoking has a bad effect on oral health ranges from mild conditions to severe forms such as oral cancer. Smoking can also cause discoloration of teeth, periodontal disease, implant failure, and dental caries. Based on these research, oral health status among smoker people is necessary to evaluate. The study aims to evaluate the oral hygiene status and caries experiences among male smokers and oral health knowledge in Benghazi City, Libya. A descriptive, cross-sectional research design based on a structured close-end questionnaire and intra oral examination (DMFT and S-OHI) were carried out among smokers. The sample was chosen from the Specialized Oral and Dental Education Center in Benghazi City. Libya, using a pre-tested, self-administered questionnaire. The data was collected and analyzed by using SPSS software. Results: It was found that more than half of the 57% of smokers are more than 35 years old. Regarding educational level, 27% of the sample had elementary level education, and 37% were college educated. Almost all of the males used cigarettes (84%), and about 55 % of the participants had poor oral hygiene. There were observed differences between the mean of caries experience and all sociodemographic data, but with simplified -oral hygiene index there were a significant association for educational level and seriocomic status only. Conclusion and Recommendations: concluded that high rates of the sample used cigarette type and half of them had poor oral hygiene status. Therefore, oral hygiene instructions should be given regularly to each smoker patient and encourage them to quit the habit of smoking. In addition, increased awareness of the roles of dentists in smoking cessation and prevention activities is needed in the dental healthcare setting of Libya. للتدخين آثار سلبية على الصحة بشكل عام، ويعتبر من عوامل الوفاة. تشير العديد من الأبحاث إلى أن للتدخين تأثيرًا سيئًا على صحة الفم يتراوح من حالة خفيفة إلى حالة خطيرة مثل سرطان الفم. كما يمكن أن يسبب التدخين تغير لون الأسنان إلى اللون البني/الأسود، وأطقم الأسنان، وترميمات الأسنان، وتغير الطعم والرائحة، وداء المبيضات الفموي، وأمراض اللثة، وفشل زراعة الأسنان، وتسوس الأسنان. وبناءً على هذه الأبحاث، من الضروري تقييم حالة صحة الفم بين المدخنين. تهدف هذه الدراسة إلى تقييم حالة نظافة الفم وتجارب التسوس بين الذكور المدخنين وصحة الفم ومعارفهم في مدينة بنغازي، ليبيا. تم إجراء تصميم بحثي وصفي مقطعي يعتمد على استبيانات مغلقة وفحص داخل الفم باستخدام مؤشرات (DMFT . OHI)بين المدخنين وتم اختيار العينة من المركز المتخصص لتعليم الفم والأسنان في بنغازي. المدينة .ليبيا . باستخدام استبيان تم اختباره مسبقًا وإدارته ذاتيًا. وتم جمع البيانات وتحليلها باستخدام برنامج SPSS. تبين أن 57% من أفراد العينة المدخنين كانت أعمارهم أكثر من 35 سنة. أما على المستوى التعليمي فقد وجد أن 27% من أفراد العينة حصلوا على مستوى ابتدائي و37% حصلوا على تعليم جامعي. اغلب الذكور استخدموا السجائر (84%). حوالي 55% من المشاركين كانوا يعانون من التهاب اللثة وهناك علاقة بين التسوس ومستوي التعليمي والمعيشي للمرضي. خلصت الدراسة الحالية إلى أن معدلات عالية من العينة تستخدم نوع السجائر ونصفهم يعانون من سوء حالة نظافة الفم والتهاب اللثة الحاد. ولذلك يجب إعطاء تعليمات نظافة الفم بانتظام لكل المرضى المدخنين وتشجيعهم على الإقلاع عن عادة التدخين. بالإضافة إلى ذلك، هناك حاجة إلى زيادة الوعي بأدوار أطباء الأسنان في أنشطة الإقلاع عن التدخين والوقاية منه في مجال الرعاية الصحية لطب الأسنان في ليبيا